On the phylogenetic relationship of South African species of Cladophora (Chlorophyta) based on the 26S (LSU) gene region - Arendse, Clement (Department of Biological Sciences, 2017)
In order to delineate the genus Cladophora in South Africa, several sites along the Cape peninsula were sampled and sequences for the partial26S region of the rRNA were obtained and a phylogram was constructed. The aims of this study were to provide a robust phylogenetic tree describing the relationship between members of the genus Cladophora and related taxa and to determine the origins of South Africa's estuarine species of Cladophora. After DNA extraction and cycle sequencing of products, sequences were aligned and compared to several east coast species (obtained from GENBANK) and a phylogram was constructed. The results yielded several clades within Cladophora; Clad. capensis grouping with Clad. isaacii, Clad sericea and Clad. dalmatica; Cheatomorpha forming a polyphyletic group within Cladophora; and Clad. vagabunda and Clad. laetevirens grouping with the estuarine species. As no Clad. vagabunda or Clad. laetevirens are found along the coast of South Africa, the origins of its estuarine species still remain a mystery and needs further investigation.